EFEKTIFITAS TRIPLE C PARENTING TERHADAP PERSEPSI PENGASUH TENTANG OBESITAS DINI ANAK USIA 3-5 TAHUN - Masita, Elly Dwi Masita; Amalia, Rizki (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
The prevalence of obesity in under-fives in Indonesia in 2013 reaches 19.1% and increases annually. In Surabaya, the prevalence of obesity in infants reaches 10.6%. Early obesity in toddlers due to several factors, among others, nutrition during pregnancy, when first providing MPASI, heredity, health, environment, perception, activity, more caloric intake. The aim of this research is to know the difference in perception between the caregiver who is given triple C parenting treatment and which is not given treatment. The type of this research is the analytical queasy experiment with the cross-sectional approach involving 60 respondents divided 30 as control respondent and 30 as respondent treatment. The sampling used purposive sampling with perception questionnaire instrument. Analysis using Mann Whitney. The results of the test obtained mean = 2.80 median = 3.00 with p = 0.001 (p <0.005). There was a significant difference in perception on caregivers who were given triple c parenting with p = 0.001